(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Background: The study of medicolegal autopsies is essential to stop the avoidable deaths at casualty in future and is helpful to develop a better healthcare system. This study is important to know death statistics and crime situation in particular area and it can address the local needs to improve the situation. Material and methods: The current study was record based analysis of autopsies at tertiary care center in Dungarpur, South Rajasthan during the one-year period of April 2018 to March 2019. A total of 229 autopsies were performed during the study period and relevant data from records had been collected. Results & Conclusion: Out of 229 cases, majority victims were male 180 (78.60%). Age group of 21-30 years, which is 3rd decade of life, having maximum number of i.e. 76 (33.19%) cases. In current study, most casualties were in the month of November. Unnatural deaths accounted for 185 (80.79%) cases and natural deaths 40 (17.47%)